New Mothers’ Experience of Caring for Premature Babies After Birth - Piro, Tiran Jamil; Ali, Ghariba Hasan; Ahmad, Hamdia Mirkhan; Saniotis, Arthur (International Journal of Psychosocial Rehabilitation, 2020)
Birth of premature babies is prevalent worldwide. Prematurity can cause women to undergo serious complications such as distress and trauma. Moreover, the special health conditions of such babies presents various post-natal challenges. The present study was carried out in order to examine the lived experiences of women with premature babies during the first weeks following childbirth. Nine postpartum women were interviewed who had given birth to preterm babies in primary health care centers and neonatal care unit in Raparin Teaching Hospital located in Erbil, the Kurdistan Region of Iraq. The women were interviewed from December 2018 to February 2019, and the collected data were analyzed using thematic analysis. Thematic analysis of the transcribed interviews generated three main themes: “Challenging responsibilities”, “Self-blame” and “Supportive medical and nursing staff”. Given the special care requirements of premature babies, medical staff and families need to provide mothers with sufficient support in order to address the challenges of this period.